2021
DOI: 10.1155/2021/9968602
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization, and Evaluation of SLN-Loaded Thermoresponsive Hydrogel System of Topotecan as Biological Macromolecule for Colorectal Delivery

Abstract: Background. Chemotherapeutic drugs cause severe toxicities if administered unprotected, without proper targeting, and controlled release. In this study, we developed topotecan- (TPT-) loaded solid lipid nanoparticles (SLNs) for their chemotherapeutic effect against colorectal cancer. The TPT-SLNs were further incorporated into a thermoresponsive hydrogel system (TRHS) (TPT-SLNs-TRHS) to ensure control release and reduce toxicity of the drug. Microemulsion technique and cold method were, respectively, used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 57 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…In contrast, the diffraction pattern of IBU-SLNs is amorphous and only characterized by large diffraction peaks, while the characteristic peaks of IBU and lipids do not exist. 40 The disappearance of IBU peak observed in the IBU-SLNs indicated that there was no IBU peak in the crystalline state in the SLNs. 41 This may be attributed to the incorporation of IBU into the lipid matrix and successful encapsulation of the drug inside the lipids.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, the diffraction pattern of IBU-SLNs is amorphous and only characterized by large diffraction peaks, while the characteristic peaks of IBU and lipids do not exist. 40 The disappearance of IBU peak observed in the IBU-SLNs indicated that there was no IBU peak in the crystalline state in the SLNs. 41 This may be attributed to the incorporation of IBU into the lipid matrix and successful encapsulation of the drug inside the lipids.…”
Section: Resultsmentioning
confidence: 95%
“…The images showed increase in the particle size with the increasing concentration of chitosan while no intraparticle interaction was observed. TEM images demonstrated the nanosize and uniform distribution of the SLNs while the influence of chitosan coating in an increase in the particle size was also observed which was due to the formation of chitosan layers over the particles [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…ZP is measured to assess the surface charge of the particle and the value ±30 mV is ideal for the stability of NPs. The sample is diluted and transferred to a cuvette (contain electrode) and placed into an instrument to analyze the result in triplicate (Xing et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%